PENGARUH PENERAPAN MODEL PEMBELAJARAN SEARCH, SOLVE CREATE AND SHARE TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK KELAS VIII SMPN 12 PADANG - Hasanah, Nurul; Mukhni, Mukhni (Jurnal Edukasi dan Penelitian Matematika, 2024)
─ The capacity to solve mathematical problems plays a significant role in the math learning process. However, students at SMPN 12 Padang showed Students at SMPN 12 Padang showed a low degree of proficiency in solving problems in mathematics. Therefore, a study was conducted to illustrate the ability of learners using the SSCS learning model to solve mathematical problems more effectively than the mathematical problem-solving abilities of learners in SMPN 12 Padang's class VIII who used the conventional learning model. Quasi-experiment with randomised posttest-only control group design. According to the data analysis results, the P-value was 0.000 and the significance level was 0.05. Due to the P-value being less than 0.05, the null hypothesis (H_0) is rejected. Thus, It may be said that learners who apply the SSCS learning model have more effective problem-solving abilities than students who use the conventional learning model.Keywords ─ Mathematical problem-solving ability, SSCS